The dynamics of legal consciousness as a factor of the transformation of reality of law - Vershok, Irina L. (Journal of the Belarusian State University. Law, 2021)
The article is devoted to the dynamics of legal consciousness in legal reality and validity. The criticism of traditionally studied universal categories (legal family, legal system, system of law) is given. Their overly schematic nature, abstracted from legal practice, and, as a result, a gap in the study of the dynamics of the corresponding phenomena are recognised. A new scheme of different ontological manifestations of law as an environment for adaptive human activity in intersubjective interaction is proposed. This is a legal reality and a legal validity. It is proved that the transformation of reality and validity of law is determined by the dynamics of legal consciousness. Legal consciousness performs the function of constructing (co-constructing) the reality and validity of law. Differences in the functioning of legal reality and legal validity depend on the characteristics of legal consciousness. The findings can be used in further fundamental studies of the problems of the ontology of law and legal consciousness, as well as in solving applied issues of improving the practice of lawmaking and law enforcement.
Keywords: legal system; legal reality; legal validity; man in the legal reality; subject in the legal validity; legal consciousness